Elinor Wight Gardner: Pioneer Geoarcheologist, Quaternary Scientist and Geomorphologist - Kathleen Nicoll (Geosciences, 2021)
Elinor Wight Gardner (1892–1981) was the first female geologist who worked and published as a geoarcheologist. During her career, she worked in arid lands of North Africa, Mediterranean and the Near East, and was regarded as a pioneering geoscientist who made important contributions in multiple fields, including archeology, geomorphology, paleontology and Quaternary science. Despite her ground-breaking work at many archeological sites, Gardner’s impact has been largely unrecognized. Few details are known about her personal life; she was a private and reserved person who left limited first-hand accounts of her opinions and motivations. Gardner worked with charismatic figures such as her life-long friend and primary collaborator, the archeologist Gertrude Caton Thompson (1888–1985). This biography synthesizes primary sources and draws insights about Gardner’s character from her bibliography, publications and notebooks, and mentions by contemporary peers. Much attention has focused on the historical “ancestral passions” of characters working in the fields of geology and archeology, with much emphasis on the ‘founding fathers’ and significantly less recognition of its ‘grandmothers’. We bring attention to the full scope of Gardner’s insightful contributions through analysis of her important collaborative research projects linking archeology and landscape studies during the early twentieth century.